Evaluasi Tingkat Pelayanan Jalan Akibat Pelebaran Pedestrian Ruas Jalan Supu Yusuf-Tabaununggu Kota Kendari - Irwan Lakawa; Vickky Anggara Ilham; Syamsuddin Syamsuddin; Heru Dwi Fitriawan (Sultra Civil Engineering Journal (SCiEJ), 2026)
This study analyzes the impact of the implementation of pedestrian zones on the level of road services on two road sections, namely Jalan Tabaununggu and Jalan Supu Yusuf. Results Before the pedestrianization, Jalan Tabaununggu had a capacity of 2586 PCU/h per direction with a degree of saturation (Q/C) of 0.49, at Service Level C. After the pedestrian zone was enforced, the capacity decreased to 2674 PCU/h with Q/C of 0.33, which indicates an increase to Service Level B. On the other hand, on Jalan Supu Yusuf, before pedestrianization, the capacity was recorded at 2998 PCU/h per direction with a Q/C of 0.43 (Service Level B). After pedestrianization, the capacity increased to 2676 PCU/h per direction and Q/C decreased to 0.34, so that the service level increased to B. These results show that the implementation of pedestrian zones has a positive impact on the stability and efficiency of traffic flow, especially on Jalan Supu Yusuf-Tabaununggu Kendari City.